The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.33308/26674874.2020342218
|View full text |Cite
|
Sign up to set email alerts
|

What Do Teachers As Adult Learners Think About MOOCs? A Case Study

Abstract: The aim of this research was to understand and interpret the opinions of teachers as adult learners on MOOCs regarding the effect of MOOC on their personal and professional development, and their motivation to attend more MOOC.  The research is a qualitative study with a holistic single case study design. Data were collected by semi-structured questions via the Google Form. At the end of the research, conclusions emerged under three themes. The first one was that the effects of MOOC on teachers’ personal devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In a European context, Vezne's (2020) case study for example explored adult learner perceptions and concluded variety, engagement, and being true to the adult educator as “facilitator” were key for a MOOC design. Still, perhaps one of the most consistent conclusions about MOOCs is that when viewed through a critical and/or social justice lens, there remains somewhat of a tension.…”
Section: Critiques Of a Mooc's “Promise”mentioning
confidence: 99%
“…In a European context, Vezne's (2020) case study for example explored adult learner perceptions and concluded variety, engagement, and being true to the adult educator as “facilitator” were key for a MOOC design. Still, perhaps one of the most consistent conclusions about MOOCs is that when viewed through a critical and/or social justice lens, there remains somewhat of a tension.…”
Section: Critiques Of a Mooc's “Promise”mentioning
confidence: 99%